An Omission Error: Missed Nursing Care - Gülcan Taşkıran Eskici; Ülkü Baykal (Association of Nurse Managers, 2021)
Missed nursing care is being explored with an increasing interest in the literature in recent years. Studies have focused on the frequency, reasons, associated factors, predicting factors and consequences of missed nursing care. The results of research conducted in many regions of the world show that the necessary nursing care is missed for various reasons. While this fact shows that missed nursing care is a global problem, it also attracts researchers around the world to focus on this issue. However, there are only two research articles investigating missed nursing care in Turkey, so further research and evidence are needed on this subject. Therefore, in this review, it was aimed to raise awareness of nurses and executive nurses on this issue and to contribute to the national literature.